ESTETIKA BAHASA TUTUR BAHASA MADURA DALAM ACARA TRADISI MANTU (Kajian Etnografi Komunikasi dalam Pelestarian Kearifan Lokal) - Sulistiyono Sulistiyono; Titik Setyowati; Dwi Sambada (Universitas Muria Kudus, 2021)
The underlying problem of the preservation of the Madurese language is twofold. First, the current phenomenon, the Madurese language as one of the local wisdom and its position as a regional language is less proud for its users. Second, the preservation of the Madurese language depends on its speakers and traditions. Madurese language has levels of mandhap, tenga’an, tenggi, and royal linguage. The traditional procession of the mantu in Madura can be used as a container for the preservation of the Madurese language. Remember, in the procession of the event there is a speech from each besan or who represents it. His speech uses various levels of speech that are in line with all levels of the listening community present. The targets of the study are as follows: (1) a description of the use of speech levels that includes good and correct choice of words, expressions, proverbs, and greetings in Madurese; (2) a description of the politeness of language and the ethics of local wisdom through the use of speech levels that include word choices, expressions, proverbs, and greetings in good and correct Madurese speech; (3) an overview of the aesthetics and sanctity of the event through the use of speech levels that include good and correct choice of words, expressions, proverbs, and greetings of the Madurese language. This is based on the study of communication ethnography on speech, namely speech situations, speech events, and speech actions. This study uses a descriptive-qualitative research approach with the following procedure. The source of data used is the speaker's speech, informants, events, and literature with data collection techniques through speech recordings, interviews, observations, and documentation. The results of the study illustrate that the use of speech levels in Madurese speech in traditional mantu events. The use of speech level in accordance with the rules of good and correct use of Madurese language has aesthetics and ethics and can be formulated in the form of speech templates.